2016
DOI: 10.1212/wnl.0000000000003396
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems and hypothalamic dopamine D3 receptor availability in Parkinson disease

Abstract: Objective: To investigate the relationship between hypothalamic D3 dopamine receptor availability and severity of sleep problems in Parkinson disease (PD).Methods: Twelve patients were assessed with PET and the high-affinity dopamine D3 receptorSeverity of sleep problems was rated with appropriate subitems of the Unified Parkinson's Disease Rating Scale part I (patient questionnaire) and the Epworth Sleepiness Scale.Results: We found that lower dopamine D3 receptor availability measured with [ 11 C]-PHNO PET w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Recently, loss of PDE4 expression has been reported in PD patients compared to healthy controls, with decreased PDE4 associated with deficits in spatial working memory [13] The hypothalamus is a critical area involved in modulating the sleep-wake cycle; the ventrolateral preoptic nucleus acts to inhibit major arousal mechanisms, thus promoting sleep [25]. Recently, the severity of EDS in PD was shown to be associated with reduced hypothalamic post-synaptic dopamine type-3 receptor (D3R) availability [5], as well as striatal dopaminergic dysfunction [4]. PDE4 regulates cAMP/PKA signalling at dopaminergic terminals subsequently modulating dopamine activity [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, loss of PDE4 expression has been reported in PD patients compared to healthy controls, with decreased PDE4 associated with deficits in spatial working memory [13] The hypothalamus is a critical area involved in modulating the sleep-wake cycle; the ventrolateral preoptic nucleus acts to inhibit major arousal mechanisms, thus promoting sleep [25]. Recently, the severity of EDS in PD was shown to be associated with reduced hypothalamic post-synaptic dopamine type-3 receptor (D3R) availability [5], as well as striatal dopaminergic dysfunction [4]. PDE4 regulates cAMP/PKA signalling at dopaminergic terminals subsequently modulating dopamine activity [11].…”
Section: Discussionmentioning
confidence: 99%
“…EDS is characterised by a tendency of rapid sleep onset during waking hours without prior drowsiness [2] and has been linked to deficits in attention and memory [3]. Positron emission tomography (PET) and singlephoton emission computed tomography (SPECT) studies have shown that dopaminergic and serotonergic dysfunction may contribute to the development of EDS in PD [4][5][6]. However, the mechanisms underlying pathophysiology of daytime sleepiness in PD remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to seek a possible explanation for why the genetically predicted increase in daytime sleepiness was associated with an increased risk of ALS. There have been studies focused on the role of daytime sleepiness in PD, in addition to a risk factor [3], daytime sleepiness has also been observed to be associated with pathological changes in hypothalamus and thalamus [26,27], which are the key positions of the center of circadian rhythms in the ascending reticular activating system [28]. Therefore, the pathophysiological process of daytime sleepiness seems to be involved in the process of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Second, a number of hypothalamic-dependent functions, such as sleep and circadian rhythmicity, are severely affected by disease progression. 3,25,26 This hypothalamic involvement could be secondary to dopaminergic 7,27,28 or serotonergic 29 and related to involvement of the autonomic nervous system. 30 In the current study, despite these repeatedly observed features of hypothalamic involvement by others, we were unable to observe gross atrophy of the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%